Preparation method of nano high-purity aluminum oxide and nano high-purity aluminum oxide
By using the continuous synthesis reaction of high-purity aluminum sulfate and ammonium bicarbonate and spray-drying two-stage roasting process when preparing nano high-purity aluminum sulfate and ammonium bicarbonate, the problem of insufficient exhaust gas emissions and performance of the traditional ammonium salt method is solved, and high purity is achieved and stability, suitable for semiconductor field.
Patent Information
- Application Number
- CN202411245292.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
The traditional ammonium salt method produces a large amount of harmful waste gases, such as ammonia, sulfur dioxide, and sulfur trioxide, and the product performance cannot meet the needs of high-end semiconductor materials.
By conducting continuous synthesis reactions of high-purity aluminum sulfate solution and high-purity ammonium bicarbonate solution at set temperature, high-purity nano-alumina hydrate was obtained, followed by spray drying and two-stage calcination, and the calcination parameters were controlled to achieve high purity and increase the content of α alumina while reducing exhaust gas emissions.
It improves the purity and application performance of nano high-purity alumina, reduces the production of waste gases such as ammonia, sulfur dioxide, and sulfur trioxide, and achieves high purity and stability of the product. It is suitable for semiconductor fields.
Smart Images

Figure CN119118172A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aluminum oxide semiconductor materials, and in particular to a method for preparing nanometer high-purity aluminum oxide and nanometer high-purity aluminum oxide. Background Art
[0002] Nano-high-purity alumina is often used in ceramic packaging substrates and chemical mechanical polishing materials in the semiconductor field due to its good insulation, thermal conductivity and mechanical properties. As the international electronic information product manufacturing industry accelerates its transfer to China, downstream companies will inevitably increase the proportion of local procurement based on procurement and transportation costs. The demand for nano-high-purity alumina in the domestic semiconductor field will increase year by year.
[0003] The commonly used large-scale production processes for nano high-purity alumina mainly include ammonium aluminum sulfate thermal decomposition method, aluminum alcohol method, modified Bayer process, etc. Among them, the aluminum alcohol method has high requirements for process equipment, and the industrial implementation process produces hydrogen and alcohol vapor, which is relatively risky; and the performance of the modified Bayer process products cannot meet the needs of high-end semiconductor materials; the ammonium aluminum sulfate thermal decomposition method first uses sulfuric acid to dissolve aluminum hydroxide to prepare aluminum sulfate, and then adds ammonium sulfate at a certain temperature, while controlling the reaction pH value, ingredient ratio and other conditions to prepare ammonium aluminum sulfate. By heating the ammonium aluminum sulfate, it will continue to dissolve in the crystallization water it carries. When the crystallization water reaches saturation, ammonium aluminum sulfate begins to precipitate. By repeatedly crystallizing ammonium aluminum sulfate, impurities such as Ca, Mg, Fe, and Si in ammonium aluminum sulfate can be removed to obtain high-purity ammonium aluminum sulfate. The resulting ammonium aluminum sulfate is then roasted at 1200 degrees Celsius to decompose into high-purity alumina when heated. The preparation process of this high-purity alumina is relatively simple to operate, and the process has been relatively mature so far. Therefore, the mature process can ensure the purity of the alumina product, and the production cost is relatively lower than other preparation processes. However, a large amount of ammonia, sulfur dioxide, sulfur trioxide and other waste gases that are harmful to the environment will be released during its preparation process, so higher requirements are placed on the treatment of tail gas during the roasting process. How to improve the application performance of nano high-purity alumina while reducing the amount of ammonia, sulfur dioxide, sulfur trioxide and other waste gases produced by the traditional ammonium salt method. Summary of the invention
[0004] The present application provides a method for preparing nano high-purity alumina and nano high-purity alumina to solve the following technical problem: how to improve the application performance of nano high-purity alumina while reducing the amount of waste gas such as ammonia, sulfur dioxide, and sulfur trioxide produced by the traditional ammonium salt method.
[0005] In a first aspect, the present application provides a method for preparing nano high-purity alumina, the method comprising:
[0006] Obtaining a high-purity aluminum sulfate solution;
[0007] The high-purity aluminum sulfate solution and the high-purity ammonium bicarbonate solution are subjected to continuous synthesis reaction at a set temperature, and then filtered and washed to obtain a high-purity nano-alumina hydrate filter cake;
[0008] The high-purity nano-alumina hydrate filter cake is configured into a slurry, and then spray-dried to obtain a high-purity nano-alumina hydrate powder; and
[0009] The high-purity nano alumina hydrate powder is calcined in two stages to obtain nano high-purity alumina.
[0010] Optionally, the high-purity aluminum sulfate solution and the high-purity ammonium bicarbonate solution are subjected to a continuous synthesis reaction at a set temperature, comprising:
[0011] The high-purity aluminum sulfate solution and the high-purity ammonium bicarbonate solution are respectively added at a uniform speed to a reaction vessel of a continuous reactor with a set temperature by a constant flow pump, and stirred and kept for a set time, so that the high-purity aluminum sulfate solution and the high-purity ammonium bicarbonate solution undergo a continuous synthesis reaction at the set temperature to obtain a white slurry;
[0012] After the white slurry fills the reaction container, the outlet of the reaction container is opened to allow the white slurry to flow out from the outlet of the reaction container.
[0013] Optionally, the set temperature is 40°C to 90°C, and the set time is 30s to 60s.
[0014] Optionally, in the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is (0.05-0.1):1.
[0015] Optionally, the stirring speed is 500 r / min to 1000 r / min.
[0016] Optionally, the spray drying temperature is 110°C to 180°C.
[0017] Optionally, the high-purity nano-alumina hydrate powder is subjected to two-stage calcination, comprising:
[0018] The high-purity nano-alumina hydrate powder is subjected to a first stage of roasting under first set parameters;
[0019] The high-purity nano-alumina hydrate powder after the first stage of calcination is subjected to a second stage of calcination with second set parameters.
[0020] Optionally, the first setting parameters include: the roasting temperature is 550℃~900℃, and the insulation time is 60min~180min; and / or, the second setting parameters include: the roasting temperature is 1100℃~1200℃, and the insulation time is 60min~180min.
[0021] Optionally, the step of obtaining a high-purity aluminum sulfate solution comprises:
[0022] Prepare a dilute sulfuric acid solution from high-purity concentrated sulfuric acid, wherein the concentration of the dilute sulfuric acid solution is 20% to 30%;
[0023] The dilute sulfuric acid solution is mixed with high-purity aluminum hydroxide, heated to boiling, and then filtered to obtain a high-purity aluminum sulfate solution; the mass of the high-purity aluminum hydroxide accounts for 10% to 20% of the mass of the dilute sulfuric acid solution.
[0024] In the second aspect, the present application provides a nano high-purity alumina prepared by the method described in any one of the embodiments of the first aspect, wherein the nano high-purity alumina satisfies at least one of the following properties: purity ≥ 99.995%, original crystal size of 100nm to 300nm, and α-alumina content of 85% to 95%.
[0025] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0026] The present application provides a method for preparing nano high-purity alumina, comprising: obtaining a high-purity aluminum sulfate solution; subjecting the high-purity aluminum sulfate solution and high-purity ammonium bicarbonate solution to continuous synthesis reaction at a set temperature, followed by filtering and washing to obtain a high-purity nano alumina hydrate filter cake; configuring the high-purity nano alumina hydrate filter cake into a slurry, followed by spray drying to obtain a high-purity nano alumina hydrate powder; and subjecting the high-purity nano alumina hydrate powder to two-stage roasting to obtain nano high-purity alumina. By controlling the purity of the raw materials, the purpose of improving the purity of the product is achieved; by controlling the continuous synthesis reaction of aluminum sulfate and ammonium bicarbonate under constant system conditions, the orderly precipitation and batch-to-batch stability of the high-purity nano alumina hydrate are ensured, and at the same time, the gas phase components in the traditional ammonium salt method precursor are converted to the liquid phase system to form ammonium salts during the reaction process, thereby increasing the alumina content in the nano alumina hydrate and avoiding the generation of waste gases such as ammonia, sulfur dioxide, and sulfur trioxide during the roasting process; and by two-stage roasting, crystal form customization is achieved. This not only reduces the amount of waste gases such as ammonia, sulfur dioxide, and sulfur trioxide produced by the traditional ammonium salt method, but also improves the application performance of nano high-purity alumina. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0028] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0029] Figure 1 A flow chart of a method for preparing nano high-purity aluminum oxide provided in an embodiment of the present application;
[0030] Figure 2 A schematic diagram of a method for preparing nano high-purity alumina provided in an embodiment of the present application. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0032] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0033] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.
[0034] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0035] Figure 1 A flow chart of a method for preparing nano high-purity aluminum oxide provided in an embodiment of the present application; Figure 2 A schematic diagram of a method for preparing nano high-purity alumina provided in an embodiment of the present application.
[0036] See also Figure 1 and Figure 2 The present application provides a method for preparing nano high-purity alumina, the method comprising:
[0037] S1, obtaining a high-purity aluminum sulfate solution;
[0038] In some embodiments, obtaining a high-purity aluminum sulfate solution comprises:
[0039] S101, preparing a dilute sulfuric acid solution from high-purity concentrated sulfuric acid, wherein the concentration of the dilute sulfuric acid solution is 20% to 30%;
[0040] S102, mixing the dilute sulfuric acid solution with high-purity aluminum hydroxide, heating to boiling, and then filtering to obtain a high-purity aluminum sulfate solution; the mass of the high-purity aluminum hydroxide accounts for 10% to 20% of the mass of the dilute sulfuric acid solution.
[0041] In some embodiments, the purity of the high-purity aluminum hydroxide is ≥99.9%, and the purity of the high-purity sulfuric acid is ≥99.9%, with a concentration of 98%.
[0042] S2, continuously synthesizing the high-purity aluminum sulfate solution and the high-purity ammonium bicarbonate solution at a set temperature, and then filtering and washing to obtain a high-purity nano-alumina hydrate filter cake;
[0043] In some embodiments, the continuous synthesis reaction of the high-purity aluminum sulfate solution and the high-purity ammonium bicarbonate solution at a set temperature comprises:
[0044] S201, respectively adding the high-purity aluminum sulfate solution and the high-purity ammonium bicarbonate solution to a reaction vessel of a continuous reactor with a set temperature through a constant flow pump at a uniform speed, and stirring and leaving for a set time, so that the high-purity aluminum sulfate solution and the high-purity ammonium bicarbonate solution undergo a continuous synthesis reaction at the set temperature to obtain a white slurry;
[0045] S202: After the white slurry fills the reaction container, open the outlet of the reaction container to allow the white slurry to flow out of the outlet of the reaction container.
[0046] In some embodiments, the method for preparing the high-purity ammonium bicarbonate solution comprises: preparing the ammonium bicarbonate into a 200 g / L solution, filtering to obtain a filtrate, and obtaining a high-purity ammonium bicarbonate solution; the purity of the high-purity ammonium bicarbonate is ≥99.9%.
[0047] In some embodiments, the set temperature is 40° C. to 90° C., and the set time is 30 s to 60 s.
[0048] In the above embodiment, the temperature and residence time of the continuous synthesis reaction system are controlled. If the temperature of the continuous synthesis reaction system is higher than 90°C, the grain size of the nano-alumina hydrate will develop abnormally after calcination; if the temperature of the continuous synthesis reaction system is lower than 40°C, the high-purity nano-alumina hydrate will be too fine, reducing the filtering and washing speed. If the residence time of the slurry in the reactor during the continuous synthesis reaction is less than 30s, the crystal form will develop irregularly after calcination phase transition, and the product uniformity will be poor; if it is higher than 60s, the grains will grow abnormally after calcination phase transition, affecting the use effect. Exemplarily, the set temperature can be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, etc., and the set time can be 30s, 35s, 40s, 45s, 50s, 55s, 60s, etc.
[0049] In some embodiments, in the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is (0.05-0.1):1.
[0050] In the above embodiment, the molar ratio of aluminum sulfate to ammonium bicarbonate is controlled to be aluminum sulfate: ammonium bicarbonate = (0.05-0.1): 1. If the molar ratio is lower than 0.05, the pH of the system is too high, and the precursor is inactivated due to the crystalline phase transition; if the molar ratio is higher than 0.1, the pH of the system is too low, and the aluminum ions are in a gel-like hydrate due to incomplete hydrolysis, which makes it difficult to achieve solid-liquid separation. Exemplarily, the molar ratio of aluminum sulfate to ammonium bicarbonate can be 0.05: 1, 0.06: 1, 0.07: 1, 0.08: 1, 0.09: 1, 0.10: 1, etc.
[0051] In some embodiments, the stirring speed is 500 r / min to 1000 r / min.
[0052] In the above embodiment, stirring is continued during the entire continuous synthesis reaction, and the stirring speed is controlled to promote uniform mixing of aluminum sulfate and ammonium bicarbonate and react, thereby increasing the reaction rate of aluminum sulfate and ammonium bicarbonate. Exemplarily, the stirring speed during the entire continuous synthesis reaction can be 500r / min, 550r / min, 600r / min, 700r / min, 800r / min, 850r / min, 900r / min, 950r / min, 1000r / min, etc.
[0053] In some embodiments, the amount of wash water is greater than 100% of the volume of the white slurry.
[0054] In the above embodiment, the amount of washing water is controlled to be more than 100% of the volume of the white slurry, so as to completely remove the precursor sulfate ions, thereby avoiding the release of polluting gases sulfur dioxide and sulfur trioxide during the phase transition process of roasting.
[0055] S3, preparing the high-purity nano-alumina hydrate filter cake into a slurry, and then spray drying it to obtain a high-purity nano-alumina hydrate powder;
[0056] In some embodiments, the spray drying temperature is 110°C to 180°C.
[0057] In the above embodiment, the spray drying temperature is controlled. If the spray drying temperature is lower than 110°C, the material cannot be dried; if the spray drying temperature is higher than 180°C, part of the nano-alumina hydrate loses water and changes phase, and the crystal form develops irregularly after calcination and changes phase, and the product uniformity is poor. Exemplarily, the spray drying temperature can be 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, etc.
[0058] S4, calcining the high-purity nano alumina hydrate powder in two stages to obtain nano high-purity alumina.
[0059] In some embodiments, the two-stage calcination of the high-purity nano-alumina hydrate powder comprises:
[0060] S401, performing a first stage roasting of the high-purity nano-alumina hydrate powder under first set parameters;
[0061] S402, subjecting the high-purity nano-alumina hydrate powder after the first stage of calcination to a second stage of calcination with second set parameters.
[0062] In some embodiments, the first setting parameters include: the roasting temperature is 550°C to 900°C, and the holding time is 60min to 180min; and / or, the second setting parameters include: the roasting temperature is 1100°C to 1200°C, and the holding time is 60min to 180min.
[0063] In the above embodiment, the temperature and time of the first stage calcination of the nano-alumina hydrate powder are controlled. If the temperature is lower than 550°C or the time is lower than 60 minutes, the nano-alumina hydrate cannot be completely converted into the γ phase; if the temperature is higher than 900°C, part of the material is converted into the θ phase; if the time is higher than 180 minutes, the production cost is increased. The temperature and time of the second stage calcination of the nano-alumina hydrate powder are controlled. If the temperature is lower than 1100°C or the time is lower than 60 minutes, the nano-alumina hydrate cannot be completely converted into the α phase; if the temperature is higher than 1200°C or the time is higher than 180 minutes, the grain size grows abnormally and the production cost is increased. Exemplarily, the temperature of the first stage of calcination can be 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, etc., and the holding time of the first stage of calcination can be 60min, 80min, 100min, 110min, 120min, 130min, 140min, 160min, 170min, 180min, etc.; the calcination temperature of the second stage of calcination is 1100°C, 1110°C, 1120°C, 1230°C, 1240°C, 1250°C, 1270°C, 1290°C, 1200°C, etc., and the holding time of the second stage of calcination can be 60min, 80min, 100min, 110min, 120min, 130min, 140min, 160min, 170min, 180min, etc.
[0064] In some embodiments, the ingredient water refers to fresh water without impurities, including but not limited to: deionized water.
[0065] Based on a general inventive concept, the present application provides a nano high-purity alumina prepared by the method described in any one of the above embodiments, wherein the nano high-purity alumina satisfies at least one of the following properties: purity ≥ 99.995%, original crystal size of 100nm to 300nm, and α-alumina content of 85% to 95%.
[0066] The present application achieves the purpose of improving the purity of the product by controlling the purity of the raw materials; in the reaction process, aluminum sulfate and ammonium bicarbonate are controlled to react continuously under constant system conditions to ensure the orderly precipitation of high-purity nano-alumina hydrate and stability between batches; in the first stage of the roasting process, the nano-alumina hydrate is controlled to be converted into γ-alumina to reduce the crystal activity, and in the second stage of roasting, the γ-alumina lattice growth is converted into α-alumina to achieve customized crystal form; in addition, in the synthesis process, the gas phase components in the traditional ammonium salt method precursor are converted into ammonium salts in the liquid phase system, and the alumina content in the nano-alumina hydrate is increased from 33% to 60-70%, and the energy consumption and production time of alumina roasting per unit mass are halved. Exemplarily, the purity of nano high-purity alumina can be 99.995%, 99.996%, 99.997%, 99.998%, 99.999%, etc., the original crystal size can be 100nm, 150nm, 200nm, 250nm, 300nm, etc., and the α-alumina content can be 85%, 86%, 87%, 88%, 89%, 90%, 92%, 94%, 95%, etc.
[0067] The nano high-purity alumina is realized based on the preparation method of the above-mentioned nano high-purity alumina. The specific steps of the preparation method of the nano high-purity alumina can refer to the above-mentioned embodiment. Since the nano high-purity alumina adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.
[0068] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0069] Example 1
[0070] This embodiment provides a method for preparing nano high-purity aluminum oxide for use in the semiconductor field, comprising the following steps:
[0071] S11. Mix a sulfuric acid solution (purity 99.9%, concentration 25%) and aluminum hydroxide (purity 99.9%) and heat to boiling, and then condense and filter to obtain an aluminum sulfate solution.
[0072] in:
[0073] The mass of aluminum hydroxide accounts for 15% of the mass of the dilute sulfuric acid solution.
[0074] S21. At 75° C., control the flow rate of aluminum sulfate solution to 100 mL / min and the flow rate of ammonium bicarbonate solution to 400 mL / min, transport them to the continuous reactor and mix with the first stirring solution for 45 seconds, react for 10 minutes to obtain a slurry, and then filter and wash the slurry to obtain a high-purity nano-alumina hydrate filter cake.
[0075] in:
[0076] In the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is 0.08:1.
[0077] The concentration of ammonium bicarbonate solution is 200g / L.
[0078] The first stirring speed is 800r / min.
[0079] The volume of water used for washing is 5L; the temperature is 25°C;
[0080] S31, adding 3000g of deionized water and a second stirring mixture to the wet cake obtained in S21 to obtain a slurry, and atomizing and drying the slurry in a spray drying tower at 120°C to obtain a nanometer high-purity alumina hydrate precursor.
[0081] in:
[0082] The second stirring speed is 300 r / min.
[0083] The temperature of deionized water was 25°C.
[0084] S41. The nano-alumina hydrate dry powder is placed in a corundum crucible with a purity of 99.9%, kept at 750° C. for 2 hours, and then kept at 1200° C. for 2 hours to obtain nano-high-purity alumina.
[0085] Example 2
[0086] This embodiment provides a method for preparing nano high-purity aluminum oxide for use in the semiconductor field, comprising the following steps:
[0087] S11. Mix a sulfuric acid solution (purity 99.9%, concentration 25%) and aluminum hydroxide (purity 99.9%) and heat to boiling, and then condense and filter to obtain an aluminum sulfate solution.
[0088] in:
[0089] The mass of aluminum hydroxide accounts for 15% of the mass of the dilute sulfuric acid solution.
[0090] S21. At 75° C., control the flow rate of aluminum sulfate solution to 100 mL / min and the flow rate of ammonium bicarbonate solution to 400 mL / min, transport them to the continuous reactor and mix with the first stirring solution for 45 seconds, react for 10 minutes to obtain a slurry, filter and wash the slurry to obtain a high-purity nano-alumina hydrate filter cake.
[0091] in:
[0092] In the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is 0.08:1.
[0093] The concentration of ammonium bicarbonate solution is 200g / L.
[0094] The first stirring speed is 800r / min.
[0095] The volume of water used for washing is 2.5L; the temperature is 25°C;
[0096] S31, adding 3000g of deionized water and a second stirring mixture to the wet cake obtained in S21 to obtain a slurry, and atomizing and drying the slurry in a spray drying tower at 120°C to obtain a nanometer high-purity alumina hydrate precursor.
[0097] in:
[0098] The second stirring speed is 300 r / min.
[0099] The temperature of deionized water was 25°C.
[0100] S41. The nano-alumina hydrate dry powder is placed in a corundum crucible with a purity of 99.9%, kept at 750° C. for 2 hours, and then kept at 1200° C. for 2 hours to obtain nano-high-purity alumina.
[0101] Example 3
[0102] This embodiment provides a method for preparing nano high-purity aluminum oxide for use in the semiconductor field, comprising the following steps:
[0103] S11. Mix a sulfuric acid solution (purity 99.9%, concentration 25%) and aluminum hydroxide (purity 99.9%) and heat to boiling, and then condense and filter to obtain an aluminum sulfate solution.
[0104] in:
[0105] The mass of aluminum hydroxide accounts for 15% of the mass of the dilute sulfuric acid solution.
[0106] S21, at 75°C, control the flow rate of aluminum sulfate solution to 100 mL / min and the flow rate of ammonium bicarbonate solution to 400 mL / min, transport them to the continuous reactor and mix with the first stirring solution for 45 seconds, react for 10 minutes, and obtain a slurry. The slurry is filtered and washed to obtain a high-purity nano-alumina hydrate filter cake.
[0107] in:
[0108] In the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is 0.08:1.
[0109] The concentration of ammonium bicarbonate solution is 200g / L.
[0110] The first stirring speed is 800r / min.
[0111] The volume of water used for washing is 5L; the temperature is 25°C;
[0112] S31, adding 3000g of deionized water and a second stirring mixture to the wet cake obtained in S21 to obtain a slurry, and atomizing and drying the slurry in a spray drying tower at 105°C to obtain a nanometer high-purity alumina hydrate precursor.
[0113] in:
[0114] The second stirring speed is 300 r / min.
[0115] The temperature of deionized water was 25°C.
[0116] S41. The nano-alumina hydrate dry powder is placed in a corundum crucible with a purity of 99.9%, kept at 750° C. for 2 hours, and then kept at 1200° C. for 2 hours to obtain nano-high-purity alumina.
[0117] Comparative Example 1
[0118] A domestic company's nano high-purity alumina product (model GNAO-05) is synthesized using the alcohol aluminum method.
[0119] Comparative Example 2
[0120] The nano high-purity alumina product (model CR-03) of a foreign company is synthesized using the ammonium salt method.
[0121] Comparative Example 3
[0122] This comparative example provides a method for preparing nano high-purity aluminum oxide for use in the semiconductor field, comprising the following steps:
[0123] S11. Mix a sulfuric acid solution (purity 99.9%, concentration 25%) and aluminum hydroxide (purity 99.9%) and heat to boiling, and then condense and filter to obtain an aluminum sulfate solution.
[0124] in:
[0125] The mass of aluminum hydroxide accounts for 15% of the mass of the dilute sulfuric acid solution.
[0126] S21, at 30°C, control the flow rate of aluminum sulfate solution to 100 mL / min and the flow rate of ammonium bicarbonate solution to 400 mL / min, transport them to the continuous reactor and mix with the first stirring for 45 seconds, react for 10 minutes, and obtain slurry. The slurry is then filtered and washed to obtain a high-purity nano-alumina hydrate filter cake.
[0127] in:
[0128] In the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is 0.08:1.
[0129] The concentration of ammonium bicarbonate solution is 200g / L.
[0130] The first stirring speed is 800r / min.
[0131] The volume of water used for washing is 5L; the temperature is 25°C;
[0132] S31, adding 3000g of deionized water and a second stirring mixture to the wet cake obtained in S21 to obtain a slurry, and atomizing and drying the slurry in a spray drying tower at 120°C to obtain a nanometer high-purity alumina hydrate precursor.
[0133] in:
[0134] The second stirring speed is 300 r / min.
[0135] The temperature of deionized water was 25°C.
[0136] S41. The nano-alumina hydrate dry powder is placed in a corundum crucible with a purity of 99.9%, kept at 750° C. for 2 hours, and then kept at 1200° C. for 2 hours to obtain nano-high-purity alumina.
[0137] Comparative Example 4
[0138] This comparative example provides a method for preparing nano high-purity aluminum oxide for use in the semiconductor field, comprising the following steps:
[0139] S11. Mix a sulfuric acid solution (purity 99.9%, concentration 25%) and aluminum hydroxide (purity 99.9%) and heat to boiling, and then condense and filter to obtain an aluminum sulfate solution.
[0140] in:
[0141] The mass of aluminum hydroxide accounts for 15% of the mass of the dilute sulfuric acid solution.
[0142] S21, at 95°C, control the flow rate of aluminum sulfate solution to 100 mL / min and the flow rate of ammonium bicarbonate solution to 400 mL / min, transport them to the continuous reactor and mix with the first stirring for 45 seconds, react for 10 minutes, and obtain slurry. The slurry is then filtered and washed to obtain a high-purity nano-alumina hydrate filter cake.
[0143] in:
[0144] In the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is 0.08:1.
[0145] The concentration of ammonium bicarbonate solution is 200g / L.
[0146] The first stirring speed is 800r / min.
[0147] The volume of water used for washing is 5L; the temperature is 25°C;
[0148] S31, adding 3000g of deionized water and a second stirring mixture to the wet cake obtained in S21 to obtain a slurry, and atomizing and drying the slurry in a spray drying tower at 120°C to obtain a nanometer high-purity alumina hydrate precursor.
[0149] in:
[0150] The second stirring speed is 300 r / min.
[0151] The temperature of deionized water was 25°C.
[0152] S41. The nano-alumina hydrate dry powder is placed in a corundum crucible with a purity of 99.9%, kept at 750° C. for 2 hours, and then kept at 1200° C. for 2 hours to obtain nano-high-purity alumina.
[0153] Comparative Example 5
[0154] This comparative example provides a method for preparing nano high-purity aluminum oxide for use in the semiconductor field, comprising the following steps:
[0155] S11. Mix a sulfuric acid solution (purity 99.9%, concentration 25%) and aluminum hydroxide (purity 99.9%) and heat to boiling, and then condense and filter to obtain an aluminum sulfate solution.
[0156] in:
[0157] The mass of aluminum hydroxide accounts for 15% of the mass of the dilute sulfuric acid solution.
[0158] S21, at 75°C, control the flow rate of aluminum sulfate solution to 100 mL / min and the flow rate of ammonium bicarbonate solution to 650 mL / min, transport them to the continuous reactor and mix with the first stirring solution for 45 seconds, react for 10 minutes, and obtain a slurry. The slurry is filtered and washed to obtain a high-purity nano-alumina hydrate filter cake.
[0159] in:
[0160] In the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is 0.04:1.
[0161] The concentration of ammonium bicarbonate solution is 200g / L.
[0162] The first stirring speed is 800r / min.
[0163] The volume of water used for washing is 5L; the temperature is 25°C;
[0164] S31, adding 3000g of deionized water and a second stirring mixture to the wet cake obtained in S21 to obtain a slurry, and atomizing and drying the slurry in a spray drying tower at 120°C to obtain a nanometer high-purity alumina hydrate precursor.
[0165] in:
[0166] The second stirring speed is 300 r / min.
[0167] The temperature of deionized water was 25°C.
[0168] S41. The nano-alumina hydrate dry powder is placed in a corundum crucible with a purity of 99.9%, kept at 750° C. for 2 hours, and then kept at 1200° C. for 2 hours to obtain nano-high-purity alumina.
[0169] Comparative Example 6
[0170] This comparative example provides a method for preparing nano high-purity aluminum oxide for use in the semiconductor field, comprising the following steps:
[0171] S11. Mix a sulfuric acid solution (purity 99.9%, concentration 25%) and aluminum hydroxide (purity 99.9%) and heat to boiling, and then condense and filter to obtain an aluminum sulfate solution.
[0172] in:
[0173] The mass of aluminum hydroxide accounts for 15% of the mass of the dilute sulfuric acid solution.
[0174] S21, at 75°C, control the flow rate of aluminum sulfate solution to 100 mL / min and the flow rate of ammonium bicarbonate solution to 200 mL / min, transport them to the continuous reactor and mix with the first stirring solution for 45 seconds, react for 10 minutes, and obtain a slurry. The slurry is filtered and washed to obtain a high-purity nano-alumina hydrate filter cake.
[0175] in:
[0176] In the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is 0.12:1.
[0177] The concentration of ammonium bicarbonate solution is 200g / L.
[0178] The first stirring speed is 800r / min.
[0179] The volume of water used for washing is 5L; the temperature is 25°C;
[0180] S31, adding 3000g of deionized water and a second stirring mixture to the wet cake obtained in S21 to obtain a slurry, and atomizing and drying the slurry in a spray drying tower at 120°C to obtain a nanometer high-purity alumina hydrate precursor.
[0181] in:
[0182] The second stirring speed is 300 r / min.
[0183] The temperature of deionized water was 25°C.
[0184] S41. The nano-alumina hydrate dry powder is placed in a corundum crucible with a purity of 99.9%, kept at 750° C. for 2 hours, and then kept at 1200° C. for 2 hours to obtain nano-high-purity alumina.
[0185] Comparative Example 7
[0186] This comparative example provides a method for preparing nano high-purity aluminum oxide for use in the semiconductor field, comprising the following steps:
[0187] S11. Mix a sulfuric acid solution (purity 99.9%, concentration 25%) and aluminum hydroxide (purity 99.9%) and heat to boiling, and then condense and filter to obtain an aluminum sulfate solution.
[0188] in:
[0189] The mass of aluminum hydroxide accounts for 15% of the mass of the dilute sulfuric acid solution.
[0190] S21, at 75°C, control the flow rate of aluminum sulfate solution to 100 mL / min and the flow rate of ammonium bicarbonate solution to 400 mL / min, transport them to the continuous reactor and mix with the first stirring solution for 45 seconds, react for 10 minutes, and obtain a slurry. The slurry is filtered and washed to obtain a high-purity nano-alumina hydrate filter cake.
[0191] in:
[0192] In the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is 0.08:1.
[0193] The concentration of ammonium bicarbonate solution is 200g / L.
[0194] The first stirring speed is 800r / min.
[0195] The volume of water used for washing is 5L; the temperature is 25°C;
[0196] S31, adding 3000g of deionized water and a second stirring mixture to the wet cake obtained in S21 to obtain a slurry, and atomizing and drying the slurry in a spray drying tower at 190°C to obtain a nano-high purity alumina hydrate precursor.
[0197] in:
[0198] The second stirring speed is 300 r / min.
[0199] The temperature of deionized water was 25°C.
[0200] S41. The nano-alumina hydrate dry powder is placed in a corundum crucible with a purity of 99.9%, kept at 750° C. for 2 hours, and then kept at 1200° C. for 2 hours to obtain nano-high-purity alumina.
[0201] Comparative Example 8
[0202] This comparative example provides a method for preparing nano high-purity aluminum oxide for use in the semiconductor field, comprising the following steps:
[0203] S11. Mix a sulfuric acid solution (purity 99.9%, concentration 25%) and aluminum hydroxide (purity 99.9%) and heat to boiling, and then condense and filter to obtain an aluminum sulfate solution.
[0204] in:
[0205] The mass of aluminum hydroxide accounts for 15% of the mass of the dilute sulfuric acid solution.
[0206] S21, at 75°C, control the flow rate of aluminum sulfate solution to 100 mL / min and the flow rate of ammonium bicarbonate solution to 400 mL / min, transport them to the continuous reactor and mix with the first stirring solution for 45 seconds, react for 10 minutes, and obtain a slurry. The slurry is filtered and washed to obtain a high-purity nano-alumina hydrate filter cake.
[0207] in:
[0208] In the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is 0.08:1.
[0209] The concentration of ammonium bicarbonate solution is 200g / L.
[0210] The first stirring speed is 800r / min.
[0211] The volume of water used for washing is 5L; the temperature is 25°C;
[0212] S31, adding 3000g of deionized water and a second stirring mixture to the wet cake obtained in S21 to obtain a slurry, and atomizing and drying the slurry in a spray drying tower at 120°C to obtain a nanometer high-purity alumina hydrate precursor.
[0213] in:
[0214] The second stirring speed is 300 r / min.
[0215] The temperature of deionized water was 25°C.
[0216] S41. The nano-alumina hydrate dry powder is placed in a corundum crucible with a purity of 99.9%, kept at 500° C. for 2 hours, and then kept at 1200° C. for 2 hours to obtain nano-high-purity alumina.
[0217] Comparative Example 9
[0218] This comparative example provides a method for preparing nano high-purity aluminum oxide for use in the semiconductor field, comprising the following steps:
[0219] S11. Mix a sulfuric acid solution (purity 99.9%, concentration 25%) and aluminum hydroxide (purity 99.9%) and heat to boiling, and then condense and filter to obtain an aluminum sulfate solution.
[0220] in:
[0221] The mass of aluminum hydroxide accounts for 15% of the mass of the dilute sulfuric acid solution.
[0222] S21, at 75°C, control the flow rate of aluminum sulfate solution to 100 mL / min and the flow rate of ammonium bicarbonate solution to 400 mL / min, transport them to the continuous reactor and mix with the first stirring solution for 45 seconds, react for 10 minutes, and obtain a slurry. The slurry is filtered and washed to obtain a high-purity nano-alumina hydrate filter cake.
[0223] in:
[0224] In the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is 0.08:1.
[0225] The concentration of ammonium bicarbonate solution is 200g / L.
[0226] The first stirring speed is 800r / min.
[0227] The volume of water used for washing is 5L; the temperature is 25°C;
[0228] S31, adding 3000g of deionized water and a second stirring mixture to the wet cake obtained in S21 to obtain a slurry, and atomizing and drying the slurry in a spray drying tower at 120°C to obtain a nanometer high-purity alumina hydrate precursor.
[0229] in:
[0230] The second stirring speed is 300 r / min.
[0231] The temperature of deionized water was 25°C.
[0232] S41. The nano-alumina hydrate dry powder is placed in a corundum crucible with a purity of 99.9%, kept at 1000° C. for 2 hours, and then kept at 1200° C. for 2 hours to obtain nano-high-purity alumina.
[0233] Comparative Example 10
[0234] This comparative example provides a method for preparing nano high-purity aluminum oxide for use in the semiconductor field, comprising the following steps:
[0235] S11. Mix a sulfuric acid solution (purity 99.9%, concentration 25%) and aluminum hydroxide (purity 99.9%) and heat to boiling, and then condense and filter to obtain an aluminum sulfate solution.
[0236] in:
[0237] The mass of aluminum hydroxide accounts for 15% of the mass of the dilute sulfuric acid solution.
[0238] S21, at 75°C, control the flow rate of aluminum sulfate solution to 100 mL / min and the flow rate of ammonium bicarbonate solution to 400 mL / min, transport them to the continuous reactor and mix with the first stirring solution for 45 seconds, react for 10 minutes, and obtain a slurry. The slurry is filtered and washed to obtain a high-purity nano-alumina hydrate filter cake.
[0239] in:
[0240] In the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is 0.08:1.
[0241] The concentration of ammonium bicarbonate solution is 200g / L.
[0242] The first stirring speed is 800r / min.
[0243] The volume of water used for washing is 5L; the temperature is 25°C;
[0244] S31, adding 3000g of deionized water and a second stirring mixture to the wet cake obtained in S21 to obtain a slurry, and atomizing and drying the slurry in a spray drying tower at 120°C to obtain a nanometer high-purity alumina hydrate precursor.
[0245] in:
[0246] The second stirring speed is 300 r / min.
[0247] The temperature of deionized water was 25°C.
[0248] S41. The nano-alumina hydrate dry powder is placed in a corundum crucible with a purity of 99.9%, kept at 750° C. for 2 hours, and then kept at 1100° C. for 2 hours to obtain nano-high-purity alumina.
[0249] Comparative Example 11
[0250] This comparative example provides a method for preparing nano high-purity aluminum oxide for use in the semiconductor field, comprising the following steps:
[0251] S11. Mix a sulfuric acid solution (purity 99.9%, concentration 25%) and aluminum hydroxide (purity 99.9%) and heat to boiling, and then condense and filter to obtain an aluminum sulfate solution.
[0252] in:
[0253] The mass of aluminum hydroxide accounts for 15% of the mass of the dilute sulfuric acid solution.
[0254] S21, at 75°C, control the flow rate of aluminum sulfate solution to 100 mL / min and the flow rate of ammonium bicarbonate solution to 400 mL / min, transport them to the continuous reactor and mix with the first stirring solution for 45 seconds, react for 10 minutes, and obtain a slurry. The slurry is filtered and washed to obtain a high-purity nano-alumina hydrate filter cake.
[0255] in:
[0256] In the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is 0.08:1.
[0257] The concentration of ammonium bicarbonate solution is 200g / L.
[0258] The first stirring speed is 800r / min.
[0259] The volume of water used for washing is 5L; the temperature is 25°C;
[0260] S31, adding 3000g of deionized water and a second stirring mixture to the wet cake obtained in S21 to obtain a slurry, and atomizing and drying the slurry in a spray drying tower at 120°C to obtain a nanometer high-purity alumina hydrate precursor.
[0261] in:
[0262] The second stirring speed is 300 r / min.
[0263] The temperature of deionized water was 25°C.
[0264] S41. The nano-alumina hydrate dry powder is placed in a corundum crucible with a purity of 99.9%, kept at 750° C. for 2 hours, and then kept at 1300° C. for 2 hours to obtain nano-high-purity alumina.
[0265] The physical and chemical indicators of the nano high-purity alumina obtained in Examples 1 to 3 and Comparative Examples 1 to 11 were tested, and the results are shown in Table 1.
[0266] Table 1 Physical and chemical indicators of nano high purity alumina
[0267]
[0268] As can be seen from Table 1, all parameters for preparing nano high-purity alumina in Example 1 are within the specified range of this application, and the comprehensive performance of nano high-purity alumina meets the requirements. The amount of washing water in Example 2 is lower than the specified range, and the drying temperature in Example 3 is lower than the specified range, but the amount of washing water and the drying temperature have little effect on the comprehensive performance of nano high-purity alumina, so the comprehensive performance of nano high-purity alumina meets the requirements. However, the synthesis temperature in Comparative Example 3 is lower than the specified range, the synthesis temperature in Comparative Example 4 is higher than the specified range, the molar ratio in Comparative Example 5 is lower than the specified range, the molar ratio in Comparative Example 6 is higher than the specified range, the drying temperature in Comparative Example 7 is higher than the specified range, the first-stage roasting temperature in Comparative Example 8 is lower than the specified range, the first-stage roasting temperature in Comparative Example 9 is higher than the specified range, the second-stage roasting temperature in Comparative Example 10 is lower than the specified range, and the second-stage roasting temperature in Comparative Example 11 is higher than the specified range, resulting in the comprehensive performance of the nano high-purity alumina of Comparative Examples 3 to 11 not meeting the requirements.
[0269] In addition, one or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0270] (1) In the embodiment of the present invention, the nano high-purity alumina obtained by the preparation process provided has a purity of more than 99.995%, an original crystal size adjustable from 100nm to 300nm, an α-alumina content adjustable from 85% to 95%, and good batch-to-batch stability. It can be used as a raw powder for packaging ceramic substrates in the semiconductor field and as a grinding medium for chemical mechanical polishing.
[0271] (2) In the embodiment of the present invention, the process synthesis provided converts the gas phase components in the traditional ammonium salt method precursor into a liquid phase system to form ammonium salt, and the alumina content in the nano alumina hydrate is increased from 33% to 60% to 70%, and the energy consumption and production time per unit mass of alumina roasting are halved.
[0272] (3) In the embodiment of the present invention, based on the traditional ammonium salt method, a continuous synthesis process of nano-alumina hydrate is developed, the gas phase components in the precursor of the traditional ammonium salt method are converted into ammonium salt and retained in the liquid phase system, and the stability between product batches can be effectively guaranteed, and the application performance of nano-high-purity alumina can be improved. And the problem of treating waste gases such as ammonia, sulfur dioxide, and sulfur trioxide generated by the traditional ammonium salt method is solved.
[0273] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing nano high-purity alumina, characterized in that: The method comprises: Obtaining a high-purity aluminum sulfate solution; The high-purity aluminum sulfate solution and the high-purity ammonium bicarbonate solution are subjected to continuous synthesis reaction at a set temperature, and then filtered and washed to obtain a high-purity nano-alumina hydrate filter cake; The high-purity nano-alumina hydrate filter cake is configured into a slurry, and then spray-dried to obtain a high-purity nano-alumina hydrate powder; and The high-purity nano alumina hydrate powder is calcined in two stages to obtain nano high-purity alumina.
2. The method according to claim 1, characterized in that The method of carrying out a continuous synthesis reaction of the high-purity aluminum sulfate solution and the high-purity ammonium bicarbonate solution at a set temperature comprises: The high-purity aluminum sulfate solution and the high-purity ammonium bicarbonate solution are respectively added at a uniform speed to a reaction vessel of a continuous reactor with a set temperature by a constant flow pump, and stirred and kept for a set time, so that the high-purity aluminum sulfate solution and the high-purity ammonium bicarbonate solution undergo a continuous synthesis reaction at the set temperature to obtain a white slurry; After the white slurry fills the reaction container, the outlet of the reaction container is opened to allow the white slurry to flow out from the outlet of the reaction container.
3. The method according to claim 2, characterized in that The set temperature is 40° C. to 90° C., and the set time is 30s to 60s.
4. The method according to claim 2, characterized in that: In the continuous synthesis reaction system, the molar ratio of aluminum sulfate to ammonium bicarbonate is (0.05-0.1):
1.
5. The method according to claim 2, characterized in that: The stirring speed is 500 r / min to 1000 r / min.
6. The method according to claim 1, characterized in that The spray drying temperature is 110°C to 180°C.
7. The method according to claim 1, characterized in that The two-stage calcination of the high-purity nano-alumina hydrate powder comprises: The high-purity nano-alumina hydrate powder is subjected to a first stage of roasting under first set parameters; The high-purity nano-alumina hydrate powder after the first stage of calcination is subjected to a second stage of calcination with second set parameters.
8. The method according to claim 7, characterized in that The first setting parameters include: the roasting temperature is 550°C to 900°C, and the insulation time is 60min to 180min; and / or, the second setting parameters include: the roasting temperature is 1100°C to 1200°C, and the insulation time is 60min to 180min.
9. The method according to claim 1, characterized in that: The method for obtaining a high-purity aluminum sulfate solution comprises: Prepare a dilute sulfuric acid solution from high-purity concentrated sulfuric acid, wherein the concentration of the dilute sulfuric acid solution is 20% to 30%; The dilute sulfuric acid solution is mixed with high-purity aluminum hydroxide, heated to boiling, and then filtered to obtain a high-purity aluminum sulfate solution; the mass of the high-purity aluminum hydroxide accounts for 10% to 20% of the mass of the dilute sulfuric acid solution.
10. A nano-high purity alumina prepared by the method according to any one of claims 1 to 9, characterized in that: The nano high-purity alumina meets at least one of the following properties: purity ≥ 99.995%, original crystal size of 100nm to 300nm, and alpha alumina content of 85% to 95%.
Citation Information
Cited By
Preparation method of nano high-purity aluminum oxide
CN120964859A
Preparation method of nano high-purity alumina
CN120964859B
